Enhancing Corporate Governance Systems through Adoption of Blockchain Technology in Small, Medium and Micro Enterprises (SMMEs) in South Africa - Nyembe, Sanele (University of the Witwatersrand, Johannesburg, 2024)
Instances of corporate fraud, exemplified by cases such as Enron in the USA,Steinhoff in Germany/South Africa, and Tongaat Hullett in South Africa, have becomeprevalent worldwide, inflicting severe repercussions on diverse stakeholders. Despitethe widespread occurrence of such frauds, they often evade early detection, resultingin substantial financial losses and erosion of shareholder value. Effective corporategovernance systems are intended to serve as the ultimate surveillance mechanism tofilter out various forms of corporate fraud.Technological advancements, particularly blockchain, hold promise for enhancingcorporate governance effectiveness. Blockchain, a digital ledger technology thatrecords transactions in immutable blocks, offers potential benefits in detecting andpreventing fraud. Importantly, blockchain technology is envisioned not as areplacement but as a complementary addition to existing corporate governancesystems to enhance their efficacy.The objective of this research was to analyse the potential impact of blockchain onSMMEs in South Africa through an online survey targeting professionals with varyingexpertise. The results of the survey, encompassing 214 respondents from diverseprofessional backgrounds including accountants, ethics committee members, boardmembers, and blockchain technology experts, revealed a consensus on the positiveimpact of blockchain integration with corporate governance pillars in curbing corporatefraud within SMMEs. The Likert scale results indicated an average score of 4.09 outof 5, suggesting a predominantly positive perception of blockchain's efficacy inaddressing corporate fraud in SMMEs. The results revealed that technologicalintervention, acting as a mediating factor between current corporate governancepractices and the capacity for early fraud detection, would yield positive outcomes. Asillustrated through the conceptual framework
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: IFRS; GAAP; SMMEs; Fraud; Conceptual Framework; Blockchain Technology; Ethics Committee; Financial Reports; Corporate Governance; UCTD; SDG-8: Decent work and economic growth